diff -r 8882d47e075f -r 2c01c0bdb385 src/HOL/Real/HahnBanach/HahnBanachExtLemmas.thy --- a/src/HOL/Real/HahnBanach/HahnBanachExtLemmas.thy Tue Jul 15 16:02:10 2008 +0200 +++ b/src/HOL/Real/HahnBanach/HahnBanachExtLemmas.thy Tue Jul 15 16:50:09 2008 +0200 @@ -40,10 +40,11 @@ *} lemma ex_xi: - includes vectorspace F + assumes "vectorspace F" assumes r: "\u v. u \ F \ v \ F \ a u \ b v" shows "\xi::real. \y \ F. a y \ xi \ xi \ b y" proof - + interpret vectorspace [F] by fact txt {* From the completeness of the reals follows: The set @{text "S = {a u. u \ F}"} has a supremum, if it is non-empty and has an upper bound. *} @@ -86,183 +87,190 @@ *} lemma h'_lf: - includes var H + var h + var E assumes h'_def: "h' \ \x. let (y, a) = SOME (y, a). x = y + a \ x0 \ y \ H in h y + a * xi" and H'_def: "H' \ H + lin x0" and HE: "H \ E" - includes linearform H h + assumes "linearform H h" assumes x0: "x0 \ H" "x0 \ E" "x0 \ 0" - includes vectorspace E + assumes E: "vectorspace E" shows "linearform H' h'" -proof - note E = `vectorspace E` - have H': "vectorspace H'" - proof (unfold H'_def) - from `x0 \ E` - have "lin x0 \ E" .. - with HE show "vectorspace (H + lin x0)" using E .. - qed - { - fix x1 x2 assume x1: "x1 \ H'" and x2: "x2 \ H'" - show "h' (x1 + x2) = h' x1 + h' x2" - proof - - from H' x1 x2 have "x1 + x2 \ H'" - by (rule vectorspace.add_closed) - with x1 x2 obtain y y1 y2 a a1 a2 where - x1x2: "x1 + x2 = y + a \ x0" and y: "y \ H" +proof - + interpret linearform [H h] by fact + interpret vectorspace [E] by fact + show ?thesis proof + note E = `vectorspace E` + have H': "vectorspace H'" + proof (unfold H'_def) + from `x0 \ E` + have "lin x0 \ E" .. + with HE show "vectorspace (H + lin x0)" using E .. + qed + { + fix x1 x2 assume x1: "x1 \ H'" and x2: "x2 \ H'" + show "h' (x1 + x2) = h' x1 + h' x2" + proof - + from H' x1 x2 have "x1 + x2 \ H'" + by (rule vectorspace.add_closed) + with x1 x2 obtain y y1 y2 a a1 a2 where + x1x2: "x1 + x2 = y + a \ x0" and y: "y \ H" and x1_rep: "x1 = y1 + a1 \ x0" and y1: "y1 \ H" and x2_rep: "x2 = y2 + a2 \ x0" and y2: "y2 \ H" - by (unfold H'_def sum_def lin_def) blast - - have ya: "y1 + y2 = y \ a1 + a2 = a" using E HE _ y x0 - proof (rule decomp_H') txt_raw {* \label{decomp-H-use} *} - from HE y1 y2 show "y1 + y2 \ H" - by (rule subspace.add_closed) - from x0 and HE y y1 y2 - have "x0 \ E" "y \ E" "y1 \ E" "y2 \ E" by auto - with x1_rep x2_rep have "(y1 + y2) + (a1 + a2) \ x0 = x1 + x2" - by (simp add: add_ac add_mult_distrib2) - also note x1x2 - finally show "(y1 + y2) + (a1 + a2) \ x0 = y + a \ x0" . + by (unfold H'_def sum_def lin_def) blast + + have ya: "y1 + y2 = y \ a1 + a2 = a" using E HE _ y x0 + proof (rule decomp_H') txt_raw {* \label{decomp-H-use} *} + from HE y1 y2 show "y1 + y2 \ H" + by (rule subspace.add_closed) + from x0 and HE y y1 y2 + have "x0 \ E" "y \ E" "y1 \ E" "y2 \ E" by auto + with x1_rep x2_rep have "(y1 + y2) + (a1 + a2) \ x0 = x1 + x2" + by (simp add: add_ac add_mult_distrib2) + also note x1x2 + finally show "(y1 + y2) + (a1 + a2) \ x0 = y + a \ x0" . + qed + + from h'_def x1x2 E HE y x0 + have "h' (x1 + x2) = h y + a * xi" + by (rule h'_definite) + also have "\ = h (y1 + y2) + (a1 + a2) * xi" + by (simp only: ya) + also from y1 y2 have "h (y1 + y2) = h y1 + h y2" + by simp + also have "\ + (a1 + a2) * xi = (h y1 + a1 * xi) + (h y2 + a2 * xi)" + by (simp add: left_distrib) + also from h'_def x1_rep E HE y1 x0 + have "h y1 + a1 * xi = h' x1" + by (rule h'_definite [symmetric]) + also from h'_def x2_rep E HE y2 x0 + have "h y2 + a2 * xi = h' x2" + by (rule h'_definite [symmetric]) + finally show ?thesis . qed - - from h'_def x1x2 E HE y x0 - have "h' (x1 + x2) = h y + a * xi" - by (rule h'_definite) - also have "\ = h (y1 + y2) + (a1 + a2) * xi" - by (simp only: ya) - also from y1 y2 have "h (y1 + y2) = h y1 + h y2" - by simp - also have "\ + (a1 + a2) * xi = (h y1 + a1 * xi) + (h y2 + a2 * xi)" - by (simp add: left_distrib) - also from h'_def x1_rep E HE y1 x0 - have "h y1 + a1 * xi = h' x1" - by (rule h'_definite [symmetric]) - also from h'_def x2_rep E HE y2 x0 - have "h y2 + a2 * xi = h' x2" - by (rule h'_definite [symmetric]) - finally show ?thesis . - qed - next - fix x1 c assume x1: "x1 \ H'" - show "h' (c \ x1) = c * (h' x1)" - proof - - from H' x1 have ax1: "c \ x1 \ H'" - by (rule vectorspace.mult_closed) - with x1 obtain y a y1 a1 where - cx1_rep: "c \ x1 = y + a \ x0" and y: "y \ H" + next + fix x1 c assume x1: "x1 \ H'" + show "h' (c \ x1) = c * (h' x1)" + proof - + from H' x1 have ax1: "c \ x1 \ H'" + by (rule vectorspace.mult_closed) + with x1 obtain y a y1 a1 where + cx1_rep: "c \ x1 = y + a \ x0" and y: "y \ H" and x1_rep: "x1 = y1 + a1 \ x0" and y1: "y1 \ H" - by (unfold H'_def sum_def lin_def) blast - - have ya: "c \ y1 = y \ c * a1 = a" using E HE _ y x0 - proof (rule decomp_H') - from HE y1 show "c \ y1 \ H" - by (rule subspace.mult_closed) - from x0 and HE y y1 - have "x0 \ E" "y \ E" "y1 \ E" by auto - with x1_rep have "c \ y1 + (c * a1) \ x0 = c \ x1" - by (simp add: mult_assoc add_mult_distrib1) - also note cx1_rep - finally show "c \ y1 + (c * a1) \ x0 = y + a \ x0" . + by (unfold H'_def sum_def lin_def) blast + + have ya: "c \ y1 = y \ c * a1 = a" using E HE _ y x0 + proof (rule decomp_H') + from HE y1 show "c \ y1 \ H" + by (rule subspace.mult_closed) + from x0 and HE y y1 + have "x0 \ E" "y \ E" "y1 \ E" by auto + with x1_rep have "c \ y1 + (c * a1) \ x0 = c \ x1" + by (simp add: mult_assoc add_mult_distrib1) + also note cx1_rep + finally show "c \ y1 + (c * a1) \ x0 = y + a \ x0" . + qed + + from h'_def cx1_rep E HE y x0 have "h' (c \ x1) = h y + a * xi" + by (rule h'_definite) + also have "\ = h (c \ y1) + (c * a1) * xi" + by (simp only: ya) + also from y1 have "h (c \ y1) = c * h y1" + by simp + also have "\ + (c * a1) * xi = c * (h y1 + a1 * xi)" + by (simp only: right_distrib) + also from h'_def x1_rep E HE y1 x0 have "h y1 + a1 * xi = h' x1" + by (rule h'_definite [symmetric]) + finally show ?thesis . qed - - from h'_def cx1_rep E HE y x0 have "h' (c \ x1) = h y + a * xi" - by (rule h'_definite) - also have "\ = h (c \ y1) + (c * a1) * xi" - by (simp only: ya) - also from y1 have "h (c \ y1) = c * h y1" - by simp - also have "\ + (c * a1) * xi = c * (h y1 + a1 * xi)" - by (simp only: right_distrib) - also from h'_def x1_rep E HE y1 x0 have "h y1 + a1 * xi = h' x1" - by (rule h'_definite [symmetric]) - finally show ?thesis . - qed - } + } + qed qed text {* \medskip The linear extension @{text h'} of @{text h} is bounded by the seminorm @{text p}. *} lemma h'_norm_pres: - includes var H + var h + var E assumes h'_def: "h' \ \x. let (y, a) = SOME (y, a). x = y + a \ x0 \ y \ H in h y + a * xi" and H'_def: "H' \ H + lin x0" and x0: "x0 \ H" "x0 \ E" "x0 \ 0" - includes vectorspace E + subspace H E + seminorm E p + linearform H h + assumes E: "vectorspace E" and HE: "subspace H E" + and "seminorm E p" and "linearform H h" assumes a: "\y \ H. h y \ p y" and a': "\y \ H. - p (y + x0) - h y \ xi \ xi \ p (y + x0) - h y" shows "\x \ H'. h' x \ p x" -proof - note E = `vectorspace E` - note HE = `subspace H E` - fix x assume x': "x \ H'" - show "h' x \ p x" - proof - - from a' have a1: "\ya \ H. - p (ya + x0) - h ya \ xi" - and a2: "\ya \ H. xi \ p (ya + x0) - h ya" by auto - from x' obtain y a where +proof - + interpret vectorspace [E] by fact + interpret subspace [H E] by fact + interpret seminorm [E p] by fact + interpret linearform [H h] by fact + show ?thesis proof + fix x assume x': "x \ H'" + show "h' x \ p x" + proof - + from a' have a1: "\ya \ H. - p (ya + x0) - h ya \ xi" + and a2: "\ya \ H. xi \ p (ya + x0) - h ya" by auto + from x' obtain y a where x_rep: "x = y + a \ x0" and y: "y \ H" - by (unfold H'_def sum_def lin_def) blast - from y have y': "y \ E" .. - from y have ay: "inverse a \ y \ H" by simp - - from h'_def x_rep E HE y x0 have "h' x = h y + a * xi" - by (rule h'_definite) - also have "\ \ p (y + a \ x0)" - proof (rule linorder_cases) - assume z: "a = 0" - then have "h y + a * xi = h y" by simp - also from a y have "\ \ p y" .. - also from x0 y' z have "p y = p (y + a \ x0)" by simp - finally show ?thesis . - next - txt {* In the case @{text "a < 0"}, we use @{text "a\<^sub>1"} - with @{text ya} taken as @{text "y / a"}: *} - assume lz: "a < 0" hence nz: "a \ 0" by simp - from a1 ay - have "- p (inverse a \ y + x0) - h (inverse a \ y) \ xi" .. - with lz have "a * xi \ + by (unfold H'_def sum_def lin_def) blast + from y have y': "y \ E" .. + from y have ay: "inverse a \ y \ H" by simp + + from h'_def x_rep E HE y x0 have "h' x = h y + a * xi" + by (rule h'_definite) + also have "\ \ p (y + a \ x0)" + proof (rule linorder_cases) + assume z: "a = 0" + then have "h y + a * xi = h y" by simp + also from a y have "\ \ p y" .. + also from x0 y' z have "p y = p (y + a \ x0)" by simp + finally show ?thesis . + next + txt {* In the case @{text "a < 0"}, we use @{text "a\<^sub>1"} + with @{text ya} taken as @{text "y / a"}: *} + assume lz: "a < 0" hence nz: "a \ 0" by simp + from a1 ay + have "- p (inverse a \ y + x0) - h (inverse a \ y) \ xi" .. + with lz have "a * xi \ a * (- p (inverse a \ y + x0) - h (inverse a \ y))" - by (simp add: mult_left_mono_neg order_less_imp_le) - - also have "\ = + by (simp add: mult_left_mono_neg order_less_imp_le) + + also have "\ = - a * (p (inverse a \ y + x0)) - a * (h (inverse a \ y))" - by (simp add: right_diff_distrib) - also from lz x0 y' have "- a * (p (inverse a \ y + x0)) = + by (simp add: right_diff_distrib) + also from lz x0 y' have "- a * (p (inverse a \ y + x0)) = p (a \ (inverse a \ y + x0))" - by (simp add: abs_homogenous) - also from nz x0 y' have "\ = p (y + a \ x0)" - by (simp add: add_mult_distrib1 mult_assoc [symmetric]) - also from nz y have "a * (h (inverse a \ y)) = h y" - by simp - finally have "a * xi \ p (y + a \ x0) - h y" . - then show ?thesis by simp - next - txt {* In the case @{text "a > 0"}, we use @{text "a\<^sub>2"} - with @{text ya} taken as @{text "y / a"}: *} - assume gz: "0 < a" hence nz: "a \ 0" by simp - from a2 ay - have "xi \ p (inverse a \ y + x0) - h (inverse a \ y)" .. - with gz have "a * xi \ + by (simp add: abs_homogenous) + also from nz x0 y' have "\ = p (y + a \ x0)" + by (simp add: add_mult_distrib1 mult_assoc [symmetric]) + also from nz y have "a * (h (inverse a \ y)) = h y" + by simp + finally have "a * xi \ p (y + a \ x0) - h y" . + then show ?thesis by simp + next + txt {* In the case @{text "a > 0"}, we use @{text "a\<^sub>2"} + with @{text ya} taken as @{text "y / a"}: *} + assume gz: "0 < a" hence nz: "a \ 0" by simp + from a2 ay + have "xi \ p (inverse a \ y + x0) - h (inverse a \ y)" .. + with gz have "a * xi \ a * (p (inverse a \ y + x0) - h (inverse a \ y))" - by simp - also have "... = a * p (inverse a \ y + x0) - a * h (inverse a \ y)" - by (simp add: right_diff_distrib) - also from gz x0 y' - have "a * p (inverse a \ y + x0) = p (a \ (inverse a \ y + x0))" - by (simp add: abs_homogenous) - also from nz x0 y' have "\ = p (y + a \ x0)" - by (simp add: add_mult_distrib1 mult_assoc [symmetric]) - also from nz y have "a * h (inverse a \ y) = h y" - by simp - finally have "a * xi \ p (y + a \ x0) - h y" . - then show ?thesis by simp + by simp + also have "... = a * p (inverse a \ y + x0) - a * h (inverse a \ y)" + by (simp add: right_diff_distrib) + also from gz x0 y' + have "a * p (inverse a \ y + x0) = p (a \ (inverse a \ y + x0))" + by (simp add: abs_homogenous) + also from nz x0 y' have "\ = p (y + a \ x0)" + by (simp add: add_mult_distrib1 mult_assoc [symmetric]) + also from nz y have "a * h (inverse a \ y) = h y" + by simp + finally have "a * xi \ p (y + a \ x0) - h y" . + then show ?thesis by simp + qed + also from x_rep have "\ = p x" by (simp only:) + finally show ?thesis . qed - also from x_rep have "\ = p x" by (simp only:) - finally show ?thesis . qed qed